Probiotic Bacillus coagulans GBI-30, 6086 reduces exercise-induced muscle damage and increases recovery - Jäger,Ralf; Shields,Kevin A.; Lowery,Ryan P.; De Souza,Eduardo O.; Partl,Jeremy M.; Hollmer,Chase; Purpura,Martin; Wilson,Jacob M. (PeerJ, 2016)
Objective. Probiotics have been reported to support healthy digestive and immune function, aid in protein absorption, and decrease inflammation. Further, a trend to increase vertical jump power has been observed following co-administration of protein and probiotics in resistance-trained subjects. However, to date the potential beneficial effect of probiotics on recovery from high intensity resistance exercise have yet to be explored. Therefore, this study examined the effect of co-administration of protein and probiotics on muscle damage, recovery and performance following a damaging exercise bout. Design. Twenty nine (n = 29) recreationally-trained males (mean ± SD; 21.5 ± 2.8 years; 89.7 ± 28.2 kg; 177.4 ± 8.0 cm) were assigned to consume either 20 g of casein (PRO) or 20 g of casein plus probiotic (1 billion CFU Bacillus coagulans GBI-30, 6086, PROBC) in a crossover, diet-controlled design. After two weeks of supplementation, perceptional measures, athletic performance, and muscle damage were analyzed following a damaging exercise bout. Results. The damaging exercise bout significantly increased muscle soreness, and reduced perceived recovery; however, PROBC significantly increased recovery at 24 and 72 h, and decreased soreness at 72 h post exercise in comparison to PRO. Perceptual measures were confirmed by increases in CK (PRO: +266.8%, p = 0.0002; PROBC: +137.7%, p = 0.01), with PROBC showing a trend towards reduced muscle damage (p = 0.08). The muscle-damaging exercise resulted in significantly increased muscle swelling and Blood Urea Nitrogen levels in both conditions with no difference between groups. The strenuous exercise significantly reduced athletic performance in PRO (Wingate Peak Power; PRO: (−39.8 watts, −5.3%, p = 0.03)), whereas PROBC maintained performance (+10.1 watts, +1.7%). Conclusions. The results provide evidence that probiotic supplementation in combination with protein tended to reduce indices of muscle damage, improves recovery, and maintains physical performance subsequent to damaging exercise.
Keywords: Gut-muscle-axis; Probiotics; Protein utilization; Athletic performance; Sports nutrition